Iodine determination in animal feed by inductively coupled plasma mass spectrometry – results of a collaborative study. Issue 2 (1st February 2021) - Jerše, Ana; Amlund, Heidi; Rasmussen, Rie R.; Sloth, Jens J.
ABSTRACT: A collaborative study was conducted in order to fully validate the performance characteristics and to evaluate the suitability of a method for determination of iodine in animal feed. The method consists of an alkaline extraction in tetramethylammonium hydroxide (TMAH) solution followed by the determination of iodine by inductively coupled plasma-mass spectrometry (ICP-MS). The method was validated for different types of feed and feed materials with a broad concentration range of 0.65–622 mg I/kg. Good agreement was found between the overall mean mass fraction values from the collaborative trial (13.8 ± 1.3 mg I/kg and 0.657 ± 0.228 mg I/kg) and the values previously determined in proficiency tests for two of the test materials (12.65 ± 2.47 mg I/kg and 0.72 ± 0.22 mg I/kg) indicating satisfactory accuracy of the method. Reproducibility standard deviations were between 7.85% and 34.65% and the HorRat values were under the acceptable limit of 2 so the between-laboratory precision was considered acceptable. Based on the statistical evaluation of the results it was concluded that the method is suitable for its intended purpose; it has been accepted as European Standard EN17050:2017 by the European Committee for Standardisation (CEN).